Interactive Audio-Visual E-Flashcards to Improve Vocabulary Mastery in English Listening Skills - Ni Putu Nirka Indriyani; Gusti Ayu Putu Sukma Trisna; Luh Sri Surya Wisma Jayanti (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2026)
English vocabulary mastery in elementary school students listening skills remains relatively low, primarily due to the limited utilization of interactive audio-visual learning media. This study aimed to develop, validate, examine the practicality of, and evaluate the effectiveness of interactive audio-visual e-flashcard media in enhancing students’ English vocabulary mastery within listening skills. The study employed a research and development approach using the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The research subject was the interactive audio-visual e-flashcard media, while the trial involved 22 fourth-grade elementary school students. Data were collected through interviews, observations, and questionnaires, with research instruments consisting of observation guidelines, rating scale sheets, and questionnaires. Data analysis included validity testing, descriptive analysis, and correlated t-tests. The findings indicated that the developed media achieved a high validity score of 3.71, while the material validity score was 3.29, both categorized as highly valid. Furthermore, the practicality results demonstrated very high qualifications, with teacher responses reaching 94%, individual student trials at 90%, and small group trials at 94%. Importantly, the effectiveness analysis revealed that the interactive audio-visual e-flashcard media was effective in improving students’ English vocabulary mastery in listening skills.